Survey Kemampuan Smash Quick dalam Permainan Bola Voli di Klub Bina Prestasi Kab. Brebes Tahun 2023 - Irfan Nawazirul Lubis; Nanang Mulyana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the quick smash ability of volleyball players at the District Achievement Development Club. Brebes. This research uses a survey method with test and measurement techniques. The results of the research show that the quick smash ability of volleyball players at the Bina Achievement Club is still not satisfactory, especially in terms of power smash, vertical jump and ball placement. However, by increasing the portion of training and motivation, the quick smash ability of volleyball players at the Achievement Development Club can be improved. This research also found that the factors that influence the success of a quick smash are speed, timing, leg muscle explosive power and body posture. The results of this research can be used as a reference to improve the quick smash ability of volleyball players at the Achievement Development Club.